2016
DOI: 10.1105/tpc.16.00439
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis SUMO E3 Ligase AtMMS21 Dissociates the E2Fa/DPa Complex in Cell Cycle Regulation

Abstract: Development requires the proper execution and regulation of the cell cycle via precise, conserved mechanisms. Critically, the E2F/DP complex controls the expression of essential genes during cell cycle transitions. Here, we discovered the molecular function of the SUMO E3 ligase METHYL METHANESULFONATE SENSITIVITY GENE21 (AtMMS21) in regulating the cell cycle via the E2Fa/DPa pathway. DPa was identified as an AtMMS21-interacting protein and AtMMS21 competes with E2Fa for interaction with DPa. Moreover, DPa is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 63 publications
0
41
0
Order By: Relevance
“…While both cohesin and condensin are also involved in checkpoint activation (24,(48)(49)(50)(51), it is unknown whether the SMC5/ 6 complex has such functions. Recently, it was reported that AtMMS21, the NSE2 subunit of SMC5/6 complex, also regulates cell cycle (52). This study tested the interactions between AtMMS21 and eight cell cycle regulators (CDKA, CYCB1; 1, RBR, E2Fa, E2Fb, E2Fc, DPa, and DPb) and found that AtMMS21 interacted with DPa.…”
Section: Loss Of E2f Function Suppresses the Sni1mentioning
confidence: 99%
“…While both cohesin and condensin are also involved in checkpoint activation (24,(48)(49)(50)(51), it is unknown whether the SMC5/ 6 complex has such functions. Recently, it was reported that AtMMS21, the NSE2 subunit of SMC5/6 complex, also regulates cell cycle (52). This study tested the interactions between AtMMS21 and eight cell cycle regulators (CDKA, CYCB1; 1, RBR, E2Fa, E2Fb, E2Fc, DPa, and DPb) and found that AtMMS21 interacted with DPa.…”
Section: Loss Of E2f Function Suppresses the Sni1mentioning
confidence: 99%
“…amino acids, from the first amino acid to the GG cleavage site) to the N terminus of NIb and then deleting the two crucial glycine residues (G92 and G93) of SUMO3 (SUMO3-ΔGG-NIb). This mutant mimics natural sumoylation of lysine residues by covalently linking SUMO to the target protein but disrupts the reversible cleavage to recycle SUMO by the desumoylation enzyme due to the deletion of the two crucial glycine residues (Ross et al, 2002;Bossis et al, 2005;Liu et al, 2016a). Wild-type NIb and SUMO3-ΔGG-NIb (both as a C-terminal YFP-tagged fusion protein) were transiently expressed in N. benthamiana leaves.…”
Section: Sumoylation Regulates the Nuclear-cytoplasmic Partitioning Omentioning
confidence: 99%
“…5). Previous reports in Arabidopsis have found that MMS21 plays a more important role in the DNA damage repair and root development [54,55]. However, MMS21 genes were expressed poorly in nearly all tissues, indicating that the role of MMS21 in peanut is mainly possibly focused on DNA repair.…”
Section: Discussionmentioning
confidence: 93%